The Makhnovist Revolution: An anarchist revolution (1917-1920) (TEL Tempo, Espaço e Linguagem, 2024)
The article aims to discuss similarities between the anarchism and the revolution that took place in the south and east of Ukraine at the beginning of the 20th century, led by makhnovists. Verifying ideological and historical hypotheses to answer the problem, the article traces a journey from the beginnings of anarchism to the context of the Makhnovist Revolution. At last, the relationship between anarchism and makhnovism proves to be intimate, despite other fundamental elements.